World Bank Group Assistance to Low-Income Fragile and Conflict-Affected States : An Independent Evaluation - Independent Evaluation Group (World Bank, Washington, DC, 2014)
Fragile and conflict-affected states (FCS) have become an important focus of World Bank Group assistance in recent years as recognition of the linkages between fragility, conflict, violence, and poverty has grown. Addressing issues of recurring conflict and political violence and helping build legitimate and accountable state institutions are central to the Bank Group's poverty reduction mission. This evaluation assesses the relevance and effectiveness of World Bank Group country strategies and assistance programs to FCS. The operationalization of the World Development Report 2011: Conflict, Security, and Development (2011 WDR) is also assessed, to see how the framework has been reflected in subsequent analytical work, country assistance strategies, and the assistance programs. The evaluation framework was derived from the concepts and priorities articulated in recent WDRs, policy papers, and progress reports issued by Bank Group management, to draw lessons from FCS. The framework is organized around the three major themes emerging from the 2011 WDR: building state capacity, building capacity of citizens, and promoting inclusive growth and jobs. The evaluation focuses on International Development Association (IDA)-only countries, which are deemed to have certain characteristics such as very low average income and no access to private finance, making them eligible for special finance tools and programs. As the benchmark for measuring results, Bank Group performance is evaluated in 33 fragile and conflict-affected states against that of 31 IDA-only countries that have never been on the FCS list. Six new country case studies; analyses of Bank Group portfolios; human resources and budget data; secondary analysis of IEG evaluations; background studies including those on aid flows, gender, private sector development, and jobs; and surveys of Bank Group staffs and stakeholders are also included in the evaluation.